Entrepreneurs Preference in Choosing Payment Method - Glisina Dwinoor Rembulan; Hendy Tannady; Gamar Al Haddar; Abu Muna Almaududi Ausat; Emy Yunita Rahma Pratiwi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
The rapid advancement of technology also affects entrepreneurial activities. An entrepreneur will definitely update or follow any existing developments so that the business is not out of date. The transactions carried out also varied. These transaction activities certainly use a variety of payment instruments, ranging from cash to non-cash. A person's preference for something is related to the reasoning process that is built in explaining the reasons for his liking for something. Preference in this sense will certainly be related to a person's opportunity to achieve something he is interested in. This type of research is descriptive research. Descriptive research is research that includes data collection by testing hypotheses or answering questions about the latest status of research subjects. From the interviews that have been conducted, it can be interpreted that entrepreneurs who choose to use cash only think that using cash only can help, those who use cash state that if the use of cash payment is in the form of cash, the form of the money can be confirmed.